Comparison between pulpotomy with MTA (made in Iran) and formocresol in primary molars of 3-6 years old children attending the department of pediatric dentistry, School of Dentistry, Medical Sciences/ University of Tehran in 2004 - Kowsari A.; Azadedel Sh; Akhondi N (Tehran University of Medical Sciences, 2007)
Background and Aim: Formocresol (FC) has been a popular pulpotomy medicament for primary dentition in recent decades. Concerns have been raised about the toxicity and potential carcinogenicity of FC, and alternatives have been proposed. Recently, the physical and biological properties of mineral trioxide aggregate (MTA) have been described in many studies. The aim of this study was to compare the success rate of pulpotomy with MTA (made in Iran) and FC in primary molars."nMaterials and Methods: In this clinical trial, 30 primary molars needing pulpotomy treatment were selected and randomly divided into two groups: (15 teeth in FC and 15 in MTA group). The teeth were then pulpotomized and restored. Clinical and radiographic results were recorded at 1-3-6-9 and 12 months and success rates of two groups were compared using Fisher’s exact test with p<0.05 as the level of significance. "nResults: After 12 months, there was no statistical significant difference between MTA group (85.8%) and FC group (93.3%) (P 1.0). The only observed radiographic failure was internal resorption. "nConclusion: Based on the results of this study, MTA can be used as an alternative to formocresol in primary teeth pulpotomy.